A new device for the prevention of pulmonary embolism in critically ill patients: Results of the European Angel Catheter Registry. Issue 3 (September 2015) - Taccone, Fabio S.; Bunker, Nicholas; Waldmann, Carl; De Backer, Daniel; Brohi, Karim; Jones, Robert G.; Vincent, Jean-Louis
Abstract : BACKGROUND: Pulmonary embolism (PE) is a potentially life-threatening complication of critical illness. In trauma and neurosurgical patients with contraindications to anticoagulation, inferior vena cava (IVC) filters have been used to prevent PE, but their associated long-term complication rates and difficulties associated with filter removal have limited their use. The Angel catheter is a temporary device, which combined an IVC filter with a triple-lumen central venous catheter (IVC filter–catheter) and is intended for bedside placement and removal when no longer indicated. METHODS: This study presents data from a European Registry of 60 critically ill patients in whom the IVC filter–catheter was used to prevent PE. The patients were all at high risk of PE development or recurrence and had contraindications to anticoagulation. The primary end points of this study were to evaluate the safety (in particular, the presence of infectious or thrombotic events) and effectiveness (the numbers of PEs and averted PEs) of the IVC filter–catheter. RESULTS: The main diagnosis before catheter insertion was major trauma in 33 patients (55%), intracerebral hemorrhage or stroke in 9 (15%), a venous thromboembolic event in 9 (15%), and active bleeding in 6 (10%). The IVC filter–catheter was placed as prophylaxis in 51 patients (85%) and as treatment in the 9 patients (15%) with venous thromboembolic event. The devices were inserted at the bedside without fluoroscopic guidance in 54 patients (90%) and within a median of 4 days after hospital admission. They were left in place for a mean of 6 days (4–8 days). One patient developed a PE, without hemodynamic compromise; two PEs were averted. No serious adverse events were reported. CONCLUSION: Early bedside placement of an IVC filter–catheter is possible, and our results suggest that this is a safe, effective alternative to short-term PE prophylaxis for high-risk patients with contraindications to anticoagulation. LEVEL OF EVIDENCE: Therapeutic study, level V.